Tiny Athletes: Enhancing Object and Self-Movement Skills Through Multi-Sports Program Among Preschoolers - Reddy, Gampala Abhigna; Daniel, A. Merlin Thanka; Oswal, Gaurav (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
This study examines the impact of a multi-sports program on enhancing object movement and Self- movement skills among preschool children. The primary objective was to assess the efficacy of the program in improving basic motor competencies, specifically in object and self-movement skills, using MOBAK (Herrmann.et.al.2018) testing instruments. Participants (N=200) were selected using a combination of simple random sampling and cluster sampling from preschools in Chennai, Bangalore, and Hyderabad. The program spanned 10 months and included a structured 30-minute class featuring warm-up exercises, rhythmic interventions, skill development activities, recreational sports, and cool down phases. Sports such as soccer, basketball, athletics, gymnastics, yoga, and cricket were included to offer a comprehensive approach to early childhood Physical Education. The study employed a paired sample t-test to analyse the differences in pre-test and post-test scores. Results indicated a significant improvement in the children’s motor skills, with mean scores increasing from 17.82 in the pre-test to 21.16 in the post-test. The calculated t-value of 6.5 surpassed the critical value of 1.97, affirming the program’s positive impact on enhancing motor skills. The multi-sports program effectively improved the physical abilities and motor skills of pre-schoolers, suggesting its potential for broader implementation. Recommendations include expanding the program to more cities, regular coachs training, parent involvement, continuous progress monitoring, and integrating additional activities for overall development.